Research of the effects of shock and vibrations on the human body - Petrović, Zoran C. (Vojnotehnički glasnik / Military Technical Courier, 2016)
There is very little reliable information about the forces needed to cause injury to the human body. Namely, it is very difficult to obtain reliable reports about the influence of mechanical forces and the subjective reaction to these forces, mainly due to the complexity and diversity of the human body in both physical and behavioral aspects. The need for the study of physical, physiological and psychological reactions of living beings in a laboratory, under controlled conditions, has led to the development and use of specialized devices for the simulation of impact and vibrations in order to carry out experiments on humans and animals. "Anthropometric" or "anthropomorphic" dummies that simulate the basic static and dynamic properties of the human body are widely used in the study of plane and car crashes. Thus, for example, a Hybrid III dummy is used in case of a frontal crash of the car. Various research works about automotive and aviation accidents as well as experiments with both dummies and living beings show that full support to the body and limiting the movement of the limbs provide maximum protection from the forces of acceleration.
Keywords: anthropometric dummy; crash; human body; vibration; shock; aircraft; accident; automobile